(untitled) - Maddock, James W; Neubeck, Gerhard (New York, 1983)
"Has also been published as Marriage & family review, volume 6, number 3/4, fall/winter 1983"--T.p. verso.; Includes bibliographies; Neal A. Newfield, Ph.D., LICSW (Giver)
Keywords: Sex -- Addresses -- essays -- lectures; Family -- Addresses -- essays -- lectures; Giới tính -- Tiểu luận và bài giảng; Gia đình -- Tiểu luận và bài giàng